Update on the global abundance and distribution of breeding Gentoo Penguins (Pygoscelis papua) - Herman, Rachael; Borowicz, Alex; Lynch, Maureen; Trathan, Phil; Hart, Tom; Lynch, Heather (Polar biology, 2020)
Though climate change is widely known to negatively affect the distribution and abundance of many species, few studies have focused on species that may benefit. Gentoo Penguin ( Pygoscelis papua ) populations have grown along the Western Antarctic Peninsula (WAP), a region accounting for ~ 30% of their global population. These trends of population growth in Gentoo Penguins are in stark contrast to those of Adélie and Chinstrap Penguins, which have experienced considerable population declines along the WAP attributed to environmental changes. The recent discovery of previously unknown Gentoo Penguin colonies along the WAP and evidence for southern range expansion since the last global assessment in 2013 motivates this review of the abundance and distribution of this species. We compiled and collated all available recent data for every known Gentoo Penguin colony in the world and report on previously unknown Gentoo Penguin colonies along the Northwestern section of the WAP. We estimate the global population of Gentoo Penguins to be 432,144 (95th CI 338,059 – 534,114) breeding pairs, with approximately 364,359 (95th CI 324,052 – 405,132) breeding pairs (85% of the population) living in the Atlantic sector. Our estimates suggest that the global population has increased by approximately 11% since 2013, with even greater increases (23%) along the WAP. The Falkland Islands population, which comprises 30% of the global population, has remained stable, though only a subset of colonies have been surveyed since the last comprehensive survey in 2010. Our assessment identifies South Georgia and sub-Antarctic islands in the Indian Ocean as being the most critical data gaps for this species.